2008
DOI: 10.1536/ihj.49.525
|View full text |Cite
|
Sign up to set email alerts
|

Locations of Coronary Artery Lesions in Patients With Severe Conduction Disturbance

Abstract: SUMMARYThe relation between conduction disturbances and coronary pathology is often uncertain. The aim of this study was to examine the location of coronary lesions in patients who have an indication for a permanent pacemaker.Between 2001 and 2006, 203 consecutive patients (121 men (59%), mean age, 65 ± 10) who had severe conduction disturbance underwent coronary angiography before pacemaker implantation. Third degree AV block was present in 172 (84%), sick sinus syndrome in 21 (11%), and Mobitz II, second deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 5 publications
2
14
1
Order By: Relevance
“…2-6)14) In the present study, type IV was the most common type of coronary pathology and type II was the second most common type in IB group; type I anatomy observed in 9.1% of patients with CAD, type II in 22.7%, type III in 15.9%, and type IV in 52.3%. In the study by Yesil et al14) the distribution of coronary pathology was 9.6% type I, 38.7% type II, 16.0% type III, and 35.0% type IV. Tandoğan et al3) studied 78 patients who had pacemaker implantation and angiographically proven CAD, and the distribution was 19% type I, 24% type II, 11% type III, and 45% type IV.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…2-6)14) In the present study, type IV was the most common type of coronary pathology and type II was the second most common type in IB group; type I anatomy observed in 9.1% of patients with CAD, type II in 22.7%, type III in 15.9%, and type IV in 52.3%. In the study by Yesil et al14) the distribution of coronary pathology was 9.6% type I, 38.7% type II, 16.0% type III, and 35.0% type IV. Tandoğan et al3) studied 78 patients who had pacemaker implantation and angiographically proven CAD, and the distribution was 19% type I, 24% type II, 11% type III, and 45% type IV.…”
Section: Discussionsupporting
confidence: 49%
“…Mosseri et al2) reported that a compromised blood flow of the septal branch and the RCA were associated with conduction disturbances. Tandoğan et al,3) Yesil et al,14) and Wei et al4) reported similar results; stenoses of septal branch from LAD or RCA are associated with AVB. However, revascularization of the stenosed coronary artery could not reverse conduction disturbances 5)6)…”
Section: Discussionmentioning
confidence: 74%
“…Although it is possible that the association between QRS duration and incident pacemaker events is due in part to underlying coronary artery disease, with lesions that may directly or indirectly compromise blood supply to the sinoatrial or atrioventricular nodes,21 our findings remained robust even after accounting for incident as well as prior myocardial infarction. Furthermore, individuals with prevalent myocardial infarction or heart failure comprised only 4% of our generally healthy, ambulatory cohort.…”
Section: Discussionmentioning
confidence: 53%
“…Several previous retrospective case control studies of selected patients with coronary artery disease who required pacemaker implantation have suggested a correlation between a specific distribution of atherosclerosis and the need for a permanent pacemaker. Cases were more likely than controls, who did not need pacemakers, to have atherosclerosis involving both the septal arteries and RCA [56][57][58]. In this case, the location of the stenosis within the proximal and mid LAD in the segment involving both the septal perforators and RCA origin would likely be seen to fit this criteria.…”
Section: Discussionmentioning
confidence: 99%